Acoustic Properties of Isotropic Hypoelastic Materials with Residual Technological Stresses; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Demidov V. N. Valery Nikolaevich (Modeling and Computational Procedures, 2016)
Title screen